PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA MANAJERIAL DENGAN SISTEM PENGUKURAN KINERJA DAN SISTEM PENGHARGAAN(REWARD) SEBAGAI VARIABEL MODERATING PADA PT. PLN DI PEKANBARU - Afif, Muhammad; Surya, R. Adri Satriawan; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to test empirically the influence of total quality management to managerial performance with performance measurement system and reward system as moderated variables, empirical study at accounting staff division in services companies in PT PLN in Pekanbaru. The data was collected by distributing questionnaires with conveniences sampling to the respondents. Samples used in this study are staff at accounting division with a total sample of 10 services companies of 106 respondent. The method analysis used in this study is multiple regression analysis.From the results of multiple regression, is one hypothesis that influence to managerial performance: 1) total quality management significantly influence on managerial performance. Meanwhile, two more hypothesis with moderated regression analysis is not influence to managerial performance, that is: 2) performance measurement system and TQM interaction have no significant influence to the managerial performance. 3) reward system and TQM interaction have no significant influence to the managerial performance.Keywords : management quality, performance, reward, and manajerial